Four novel polymorphisms in long non-coding RNA HOTTIP are associated with the risk and prognosis of colorectal cancer. Issue 5 (7th May 2019) - Lv, Zhi; Xu, Qian; Sun, Liping; Wen, Jing; Fang, Xinxin; Xing, Chengzhong; Yuan, Yuan
Abstract : Background: The role of long non-coding RNA (lncRNA) HOXA transcript at the distal tip (HOTTIP) as an oncogene in varieties of human cancer including colorectal cancer (CRC) has been extensively researched. The expression and function of lncRNAs could be affected by single nucleotide polymorphisms (SNPs), which are associated with cancer susceptibility and prognosis. However, no investigation has focused on the association between HOTTIP SNPs and CRC. The aim of the present study was to explore the association of polymorphisms in the lncRNA HOTTIP gene with CRC risk and prognosis. Methods: A total of 1848 subjects were enrolled in our study, including 884 CRC cases and 964 controls. Genotyping for five HOTTIP tagSNPs (rs3807598, rs17501292, rs2067087, rs17427960, and rs78248039) was performed by applying Kompetitive allele specific PCR (KASP). Results: The results showed three SNPs (rs3807598, rs2067087, and rs17427960) were associated with enhanced CRC risk both in overall and stratified analysis. One polymorphism, rs17501292, could improve the overall survival (OS) of CRC patients in the tumor of ulcerative/invasive-type subgroup. Conclusion: These findings suggest HOTTIP SNPs could potentially be predictive biomarkers for CRC risk and prognosis. The present study provides clues for further exploration of novel lncRNA-based genetic biomarkers to predict CRC susceptibility as well as clinical outcome.